Mathematics
brynncummins
2016-09-26 19:34:06
Please solve step by step
ANSWERS
superkid4u
2016-09-26 22:10:11

First we need to get rid of the fraction. We get rid of fractions by multiplying by the RECIPROCAL aka, flipping the fraction. Like this:  [latex](x+3)^ frac{3}{2} ^*^ frac{2}{3} =27^ frac{2}{3} [/latex] Now we have:   x+3=9 Subtract 3 from both sides to isolate x:  [latex]x+3-3=9-3 [/latex] Final answer: x=6

Hunter5025
2016-09-26 22:11:26

(x+3) 3/2=27    (x)(‌3/2‌)+(3)(‌3/2‌)=27(Distribute)‌  3/2‌x+‌9/2‌=27  Subtract 9/2 from both sides.‌ 3/2‌x+‌9/2‌−‌9/2‌=27−‌9/2‌‌  3/2‌x=‌45/2‌ Multiply both sides by 2/3.  (‌2/3‌)*(‌3/2‌x)=(‌2/3‌)*(‌45/2‌)  x=15  Answer: x=15

ADD ANSWER